A Jurassic mammal from South America - Rauhut, Oliver Walter Mischa (2002)
The Jurassic period is an important stage in early mammalian evolution, as it saw the first diversification of this group, leading to the stem lineages of monotremes and modern therian mammals. However, the fossil record of Jurassic mammals is extremely poor, particularly in the southern continents. Jurassic mammals from Gondwanaland are so far only known from Tanzania and Madagascar, and from trackway evidence from Argentina. Here we report a Jurassic mammal represented by a dentary, which is the first, to our knowledge, from South America. The tiny fossil from the Middle to Late Jurassic of Patagonia is a representative of the recently termed Australosphenida, a group of mammals from Gondwanaland that evolved tribosphenic molars convergently to the Northern Hemisphere Tribosphenida, and probably gave rise to the monotremes. Together with other mammalian evidence from the Southern Hemisphere, the discovery of this new mammal indicates that the Australosphenida had diversified and were widespread in Gondwanaland well before the end of the Jurassic, and that mammalian faunas from the Southern Hemisphere already showed a marked distinction from their northern counterparts by the Middle to Late Jurassic.